FILM DOKUMENTER SEBAGAI KATALIS PERUBAHAN SOSIAL: STUDI KASUS AMBON, ACEH DAN BALI - Budi Irawanto; Theresia Octastefani (Universitas Gadjah Mada, 2019)
Since democratization (Reformasi) in 1998, documentary films gradually evolve with their locus of production spreading across the Indonesian archipelago. With the spirit of democratization brought about by digital technology, film communities and civil organizations in outer islands of Java utilize digital documentary film to capture several pertinent socio-political issues and raise public and government attention and responses. Those issues are commonly overlooked by the local media and were never a part of local government’s policies. Based on our fieldwork conducted in three areas outside of the Java Island (Ambon, Aceh and Bali), where digital documentary filmmaking and civil organizations are active and vibrant, our study indicates that rather than simply producing documentaries, film communities or non-governmental organizations disseminated documentaries through public screenings to invite further engagement of audiences by discussing the film with authorities (policy makers) that were often invited in that event. In this article, we attempt to illuminate how documentary filmmaking allows the unseen and neglected issues to be articulated visually and sonically. Therefore, it would be compelling public or media attention and encouraging further government policy to resolve that matters. In other words, documentary films are a catalyst for social change by taking their roles as witness for the public and demanding responsibilities of the political authority.